"In the Room Where It Happens:" Advocacy 101 for Literacy Leaders. (8th November 2022) - Gómez, Margarita; Saal, Leah Katherine
Abstract: As literacy leaders, we know that printed words carry great meaning and power. Today, there is a widespread belief that advocacy over government concerns or policies can be adequately achieved using social media. While a well‐timed and phrased social media post can supplement advocacy efforts, advocacy must be driven by deeds even more than words. In this article, the authors articulate the importance of face‐to‐face policy advocacy with elected officials to address any educational, health, or social policy in your locale which impacts the students, families, and communities you belong to and/or serve. Specifically, they outline the steps for advocating directly with an elected legislative official (or their staff representative) and provide numerous exemplars of documents as mentor texts to support and supplement policy advocacy efforts. Their models actualize policy advocacy for socially just practices that impact some of the most vulnerable populations, English learners, and associated funding for programs supporting these populations also known as English to Speakers of Other Languages (ELs/ESOL).